2021
DOI: 10.1007/s00404-021-06305-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic predictors in recurrent adult granulosa cell tumors of the ovary: a systematic review and meta-analysis

Abstract: Background Ovarian adult granulosa cell tumours are low-grade malignant sex cord-stromal neoplasm with a low recurrence rate. Prognostic factors for recurrence include tumor stage, tumor rupture in Stage I neoplasms and the presence of residual tumors after surgery. However, in recurrent tumors, prognostic factors for overall survival (OS) are lacking. In the present paper, we conducted a systematic meta-analysis with the aim to assess prognostic factors for OS in patients with recurrent GCT. Methods Electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Consistent with the above studies, this study found that more than 75% of patients presented with pelvic and abdominal recurrence, with abdominal or pelvic mass and liver metastasis being the most common situation. Moreover, relapse pattern (distant lesion) was also considered a prognostic factor of secondary recurrence in this study, and similar results were observed in another study 17 . Therefore, recurrence during first 5‐year follow‐up and additional recurrence within 33 months since the first recurrence illustrate unfavorable prognosis in patients with AGCT.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with the above studies, this study found that more than 75% of patients presented with pelvic and abdominal recurrence, with abdominal or pelvic mass and liver metastasis being the most common situation. Moreover, relapse pattern (distant lesion) was also considered a prognostic factor of secondary recurrence in this study, and similar results were observed in another study 17 . Therefore, recurrence during first 5‐year follow‐up and additional recurrence within 33 months since the first recurrence illustrate unfavorable prognosis in patients with AGCT.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, relapse pattern (distant lesion) was also considered a prognostic factor of secondary recurrence in this study, and similar results were observed in another study. 17 Therefore, recurrence during first 5‐year follow‐up and additional recurrence within 33 months since the first recurrence illustrate unfavorable prognosis in patients with AGCT. Hence, a long period of regular follow‐up is recommended to monitor pelvic abdominal status.…”
Section: Discussionmentioning
confidence: 99%
“…From the 95% 5-year survival rate at stage I, survival drops to 55% to 75% at stage II, and further down to 22% to 50% at stage III ( 27 ). A recent study also showed that an anatomic site of recurrence outside the pelvis was associated with a worse prognosis ( 36 ).…”
Section: Granulosa Cell Tumorsmentioning
confidence: 99%
“…7 Whether surgery is more effective than chemotherapy or radiotherapy is unknown. [8][9][10][11][12] Cytotoxic platinum-based chemotherapy (CT) is recommended for treating metastatic or recurrent AOGCT. The objective response rates (RRs) to multiple combined chemotherapy regimens have been reported to range from 50% to 92%; [13][14][15] however, durable remission is infrequent.…”
Section: Introductionmentioning
confidence: 99%